1995
DOI: 10.1007/bf00357691
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of karyotypes of muntjacs by chromosome painting

Abstract: We have used a combination of chromosome sorting, degenerate oligonucleotide-primed polymerase chain reaction (DOP-PCR), chromosome painting and digital image capturing and processing techniques for comparative chromosome analysis of members of the genus Muntiacus. Chromosome-specific "paints" from a female Indian muntjac were hybridised to the metaphase chromosomes of the Gongshan, Black, and Chinese muntjac by both single and three colour chromosome painting. Karyotypes and idiograms for the Indian, Gongshan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
144
0
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 234 publications
(152 citation statements)
references
References 25 publications
4
144
0
4
Order By: Relevance
“…Accordingly, the chromosome pair 3 was heteromorphic (3a3b) which is the first time this has been reported (Figs. 4,5), with former studies showing NORs in 4 sites, on chromosome pairs 1 and 3 (Yang et al 1995, Suwattana et al 1996, Burkin et al 1997, Tanomtong et al 2005. For male M. muntjak, NORs were found in 4 sites on nearly as telomeres of the q arm in both chromosome pair 1 and q arm on both chromosome pair 3 which agrees with the results of Goodpasture and Bloom (1975), Levy et al (1993) and Tanomtong et al (2005), but which differs from the report by Ved Brat et al (1979).…”
Section: Chromosome Markers Of Indian Muntjac (M Muntjak) In Laos Pdrsupporting
confidence: 62%
See 1 more Smart Citation
“…Accordingly, the chromosome pair 3 was heteromorphic (3a3b) which is the first time this has been reported (Figs. 4,5), with former studies showing NORs in 4 sites, on chromosome pairs 1 and 3 (Yang et al 1995, Suwattana et al 1996, Burkin et al 1997, Tanomtong et al 2005. For male M. muntjak, NORs were found in 4 sites on nearly as telomeres of the q arm in both chromosome pair 1 and q arm on both chromosome pair 3 which agrees with the results of Goodpasture and Bloom (1975), Levy et al (1993) and Tanomtong et al (2005), but which differs from the report by Ved Brat et al (1979).…”
Section: Chromosome Markers Of Indian Muntjac (M Muntjak) In Laos Pdrsupporting
confidence: 62%
“…The data showed 149 and 192 bands, respectively which are higher than the studies of Yang et al (1995), Burkin et al (1997), Ved Brat et al (1979 and Levy et al (1992). All these authors reported that the number of chromosome bands of the Indian muntjac, M. muntjak, were 82, 108 and 105 bands, respectively.…”
Section: Number Of Chromosome Bands Of Indian Muntjac (M Muntjak) Inmentioning
confidence: 69%
“…1b), 23 hybridized to a single chromosome (nos. 2,3,5,6,7,7,8,10,11,13,15,16,17,20,21,23,24,24,25,26,27, X, and the Y) when painted to G-banded elephant chromosomes. The homologues of chromosomes 7 and 24 were each separated into a different peak due to differences in the amounts of heterochromatin between the respective homologues of each pair.…”
Section: Resultsmentioning
confidence: 99%
“…Comparative chromosome painting between human and aardvark, and human and elephant was performed as previously described (22)(23)(24). In brief, 100-150 ng of biotin-labeled chromosome-specific paints were made up to 12 ml with hybridization buffer (50% deionized formamide͞10% dextran sulfate͞2ϫ SSC͞0.5 M phosphate buffer, pH 7.3͞1ϫ Denhardt's solution).…”
Section: Methodsmentioning
confidence: 99%
“…Although different mammals display very different karyotype organizations in the size and shape of their chromosomes, large blocks of DNA retain considerable sequence homology across species. With some minor experimental modification, chromosome paints from one species can be used to highlight homologous blocks of DNA in a second species and vice versa (40,41). Reciprocal cross-species painting experiments have allowed the major chromosome rearrangements that have occurred during speciation to be directly visualized and the karyotype of common ancestral karyotypes to be inferred (42).…”
Section: Karyotype Evolution Viamentioning
confidence: 99%